2010
DOI: 10.1016/j.jacc.2009.10.092
|View full text |Cite
|
Sign up to set email alerts
|

Gene Dosage of the Common Variant 9p21 Predicts Severity of Coronary Artery Disease

Abstract: Gene dosage of the common risk variant 9p21 predicts the severity of coronary atheromatous burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 24 publications
6
126
1
4
Order By: Relevance
“…While the molecular mechanism of 9p21 is unknown, its site of action has been confirmed. All studies have consistently shown the 9p21 risk variant relates to coronary atherosclerosis and only secondarily to myocardial infarction (32), (33), (34), (35). Some studies have also suggested 9p21 to be associated with the rate of progression of coronary atherosclerosis(32), (35).…”
Section: Discovery Of 9p21 the First Genetic Risk Variant Associatedmentioning
confidence: 99%
“…While the molecular mechanism of 9p21 is unknown, its site of action has been confirmed. All studies have consistently shown the 9p21 risk variant relates to coronary atherosclerosis and only secondarily to myocardial infarction (32), (33), (34), (35). Some studies have also suggested 9p21 to be associated with the rate of progression of coronary atherosclerosis(32), (35).…”
Section: Discovery Of 9p21 the First Genetic Risk Variant Associatedmentioning
confidence: 99%
“…The fact that 23 of the 36 risk variables for CHD do not act through any of the known risk factors indicates unknown mechanisms that need to be elucidated. 33 In another review of 35 common variables that affect CHD, the risk for disease did not exceed 13% of the total heritability of CHD. 34 All these findings suggest that there are still many things to be discovered.…”
Section: Genome-wide Association Studymentioning
confidence: 97%
“…A similar analysis with coronary angiography was also performed with 517 patients with late-onset CAD. Approximately 50% of the patients had myocardial infarction superimposed on the atherosclerosis (46 ). The analysis of the 9p21 variant as a risk factor indicated a strong association with coronary atherosclerosis, and 9p21 was a predictor of severity, as assessed by the number of vessels involved (46 ).…”
Section: The Site Of Action For the 9p21 Variant Is The Vessel Wallmentioning
confidence: 98%
“…Approximately 50% of the patients had myocardial infarction superimposed on the atherosclerosis (46 ). The analysis of the 9p21 variant as a risk factor indicated a strong association with coronary atherosclerosis, and 9p21 was a predictor of severity, as assessed by the number of vessels involved (46 ). Individuals with single-vessel disease had the lowest dose of 9p21 risk, whereas individuals with 3-vessel disease had the highest frequency of 2 copies of the 9p21 risk allele.…”
Section: The Site Of Action For the 9p21 Variant Is The Vessel Wallmentioning
confidence: 99%